Winner in the ring: Advantages of the Watusi collar in management of post-burn neck scar contractures. Issue 1 (July 2017) - Nosanov, Lauren B.; Allely, Rebekah R.; Beyene, Robel T.; Walters, E. Shannon; Shupp, Jeffrey W.
Highlights: A historical review of neck splinting for burn scar contractures is presented. Methodology for Watusi collar construction is described, with adaptations. Case series presentation highlighting utility and efficacy. Translation to an international outreach program. Abstract: Objective: Burns to the neck are prone to the development of scarring and contracture. In addition to other modalities of rehabilitation, effective splinting is crucial in the achievement of optimal functional outcomes. This paper describes the use of the custom-made Watusi collar in patients with neck burns. Methods: Methods of splint manufacture are described, based on current institutional therapist practice. A series of patients with neck burns managed by splinting with the Watusi collar are discussed, as are patients treated in outreach efforts to Malawi. Results: Patients treated with the Watusi collar at a Burn Center as well as those managed by local practitioners in Malawi found the splint to be more comfortable than alternatives and therefore were compliant with their use. Care providers in Malawi were affordably and easily able to adapt the Watusi collar to available materials. Conclusions: The Watusi collar is a valuable option for the management of neck scars and contractures after burn injury. These splints are affordable, customizable and enable compliance through increased patient comfort. Initial international outreach efforts demonstrate potential benefits of these collars in resource-limited regions.